0
$\begingroup$

$$xy'' + 2y' = 12x^2$$

Solve this by substituting $u = y'$

When I do this I get $u = y' = \frac{4x^3 + C}{2x}$

How do I continue?

Thanks

$\endgroup$
  • 1
    $\begingroup$ separating variables equation $y' =\frac{4x^3 + C}{2x}\Rightarrow dy=\frac{4x^3 + C}{2x}dx$ $\endgroup$ – R.N Oct 23 '15 at 9:25
  • $\begingroup$ And what am I supposed to do with that information? $\endgroup$ – John Snoe Oct 23 '15 at 9:32
  • $\begingroup$ I'm not sure your solution for $u$ is correct. $\endgroup$ – Matthew Leingang Oct 23 '15 at 9:33
1
$\begingroup$

Letting $u=y'$ gives an an equation for $u$: $$ x u' + 2u = 12 x^2 \implies u' + \frac{2}{x} u = 12x $$ This differential equation is linear with integrating factor $$ p = e^{\int \frac{2}{x}\,dx} = e^{2 \ln x} = x^2 $$ Multiplying through we have \begin{align*} x^2 u' + 2x u &= 12x^3 \\ \implies (x^2u)' &= 12x^3 \\ \implies x^2 u &= 3x^4+ C \\ \implies u &= 3x^2 + \frac{C}{x^2} \end{align*} You can check that $u$ satisfies the desired equation, for \begin{align*} u' &= 6x - \frac{2C}{x^3} \\ xu' &= 6x^2 - \frac{2C}{x^2} \\ 2u &= 6x^2 + \frac{2C}{x^2} \\ \end{align*} The sum of the RHS of the last two equations is $12x^2$.

But you wanted $y$, not $u$. No problem; we know $$ y' = 3x^2 + Cx^{-2} \implies y = x^3 - C x^{-1} + D = x^3 - \frac{C}{x} + D $$ You can check this $y$ function satisfies your original DE.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.